Implementation of ecopreneurship-oriented project-based learning (pbl) to improve the entrepreneurial spirit and student learning outcomes - Ana Rokhmawati; Puji Savvy Dian Faizati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
The Environmental Knowledge course is a compulsory subject for STKIP PGRI Lumajang students. The value of student learning outcomes in this subject is low. In addition, based on the results of the questionnaire, it is known that the entrepreneurial spirit of students is low. The objective of this research is to improve the entrepreneurial spirit and student learning outcomes through ecopreneurship-oriented project-based learning. This type of research is classroom action research. The subjects in this research were students of Mathematics Education STKIP PGRI Lumajang class 2019. The research instrument used was an entrepreneurial spirit observation sheet with a rating scale and cognitive learning outcomes test questions. There are 13 test questions in this research. Data collection techniques using observation and tests. Based on the results of the research showed that the entrepreneurial spirit of students in the first cycle was 77.24 and in the second cycle was 83.90. Student learning outcomes in the first cycle of 73.96 and the second cycle of 80.54. This shows that the implementation of ecopreneurship-oriented project-based learning improves the entrepreneurial spirit and student learning outcomes of STKIP PGRI Lumajang in the Environmental Knowledge course.